(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Acute diffuse peritonitis (ADP) is a severe and life-threatening surgical emergency associated with high mortality, systemic inflammatory response, and complex pathophysiological mechanisms. One of the critical factors influencing the clinical course and prognosis of ADP is the development of hepatic dysfunction. However, the exact mechanisms of liver damage in the context of peritonitis and the efficacy of therapeutic interventions aimed at protecting and restoring liver function remain insufficiently investigated. This study aims to evaluate the impact of specialized amino acid infusions—glutamine, arginine, and branched-chain amino acids (BCAA)—on liver function and clinical outcomes in patients with acute diffuse peritonitis.